2019
DOI: 10.3390/molecules24213833
|View full text |Cite
|
Sign up to set email alerts
|

An Amphiphilic Pyridinoyl-hydrazone Probe for Colorimetric and Fluorescence pH Sensing

Abstract: A new pH sensor based on a substituted aroylhydrazide with a flexible side chain and a terminal trimethyl ammonium group (PHA+) was designed and synthesized. The terminal quaternary ammonium guarantees excellent solubility in water. At the same time, the probe is very soluble in hydrophobic envirornments. The pyridinoyl-hydrazone moiety acts as the pH-sensitive fluorophore/chromophore probe. Extensive physicochemical characterization has been performed on the bromide salt PHABr. DFT calculations, based on sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 68 publications
0
19
0
Order By: Relevance
“…All starting products were commercially available. 5-(4-Formyl-3-hydroxyphenoxy)-N,N,Ntrimethylpentan-1-aminium bromide [24] was obtained as described in the literature. Benzothiazole-2-carboxylic acid hydrazide [25] was obtained by common synthetic route placing ethyl benzothiazole-2-carboxylate under reflux in ethanol with an excess of hydrazine for 1 h.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All starting products were commercially available. 5-(4-Formyl-3-hydroxyphenoxy)-N,N,Ntrimethylpentan-1-aminium bromide [24] was obtained as described in the literature. Benzothiazole-2-carboxylic acid hydrazide [25] was obtained by common synthetic route placing ethyl benzothiazole-2-carboxylate under reflux in ethanol with an excess of hydrazine for 1 h.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we designed and synthesized an amphiphilic picolinoyl-hydrazone-based sensor [24] with a charged side chain capable of guaranteeing water solubility. In that study, we checked the effect of the heterocycle on the spectroscopic response involving pH determination.…”
Section: Introductionmentioning
confidence: 99%
“…The use of optical probes for non-electrochemical pH determination is common in complex biological systems [ 92 ]. Diana et al synthesized and characterized a new pH sensitive fluorescent molecule (5-(4-formyl-3-hydroxyphenoxy)- N , N , N -trimethylpentan-1-aminium bromide, PHABr), which changes from transparent to yellow at pH above 7 with increased fluorescence [ 93 ]. The experimental photophysical characterization was carried out in solution, and no relevant probe-membrane interaction measurements were performed.…”
Section: Charge-transfer-based and Other Solvatochromic Probesmentioning
confidence: 99%
“…These methods require the use of fluorescent probes, able to penetrate the membranes allowing a precise and immediate analysis [ 2 , 3 ]. The number of probes developed for the study of raft membranes is continuously increasing; those so far reported have restrictions related to the type of membrane and the fluorescence technique used [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most recently identified class of probes corresponds to the class of environment-sensitive probes, which can directly distinguish the Lo and Ld phases due to differences in their intrinsic properties. These probes can change their fluorescence properties, fluorescence intensity, and even the emission color in response to changes in the environment [ 5 , 7 , 8 , 9 ]. This class includes solvatochromic fluorescent probes that show variations in their fluorescence properties depending on the polarity and hydration of the environment.…”
Section: Introductionmentioning
confidence: 99%